Sulfurized Carbon Composite with Unprecedentedly High Tap Density for Sodium Storage. Issue 7 (29th December 2021) - Jo, Chang‐Heum; Yu, Jun Ho; Kim, Hee Jae; Hwang, Jang‐Yeon; Kim, Ji‐Young; Jung, Hun‐Gi; Myung, Seung‐Taek
Abstract: A novel sulfurized carbon decorated by terephthalic acid (TPA) and polyacrylonitrile (PAN), with unprecedently high tap density (≈1.02 g cm −3 ), is investigated. Room‐temperature sodium–sulfur batteries offer high energy density; however, the dissolution of the polysulfide is a major factor hindering their commercialization. This dissolution problem can be tolerated by inhibiting the formation of polysulfide through binding sulfur to the carbon structure of PAN. Low sulfur content and low volumetric energy density in the composite are other drawbacks to be resolved. Heat‐treated TPA induces a high‐density carbonaceous material with high conductivity. This TPA is partly replaced by PAN, and the produced carbon and sulfur are composited with dehydrated polyacrylonitrile (CS–DPAN), which exhibits higher conductivity and surface area than the sulfurized dehydrated polyacrylonitrile (S–DPAN). The CS–DPAN composite electrode exhibits excellent electrochemical performance, and the resulting volumetric capacity is also superior to that of the S–DPAN material electrode. Operando Raman and operando X‐ray diffraction analyses confirm that the increased capacity is realized via the avoidance of parasitic C60 Na3 formation formed below 1 V, by adjusting the operation voltage range. This finding demonstrates the feasibility of carbon–sulfur composites as a high‐energy electrode material for rechargeable sodium batteries. Abstract : Terephthalic acid is composited with polyacrylonitrile, resulting in unprecedently high tap density. Avoiding formation of parasitic sodiated carbon below 1 V, the sulfur composite electrode ensures long‐term cyclability with 96% retention for 500 cycles. This finding demonstrates the feasibility of rechargeable sodium–sulfur batteries.